Analysis of the effectiveness of combining high-and low-thrust engines in Earth – Mars flights - Харитонов, Олексій; Куценко, Олексій; Куценко, Анастасія (Київський національний університет імені Тараса Шевченка, 2025)
Interplanetary manned flights require rapid and economical implementation. These requirements can be met by combining high-thrust and low-thrust engines, which can provide the necessary power and energy efficiency. The problem of a "sprint" flight from Earth to Mars is considered, which consists in transferring a spacecraft from a given circular geocentric orbit to a given circular areocentric orbit in a given time, less than the time of a classic Hohmann-type transfer. The combination of high-thrust and low-thrust engines leads to the problem of optimizing the distribution of the total Δv budget between the high-thrust and low-thrust maneuvers. At the same time, the heliocentric part is formed by the low-thrust engine and differs from the usual Keplerian arc. The high-thrust engine provides maneuvers in the spheres of influence of the planets. Thanks to this, compared to the classic option of using only high thrust, the total maneuver time does not change, and part of the fuel is used by a more efficient low-thrust system. This raises the question: under what conditions will the mass of fuel saved in this way exceed the mass of the additionally installed low-thrust propulsion system? The paper provides an estimate of flight duration, which assesses the upper limit of the flight duration range in which the combination of high- and low-thrust engines is optimal. Pages of the article in the issue: 142 - 145 Language of the article: Ukrainian

Міжпланетні пілотовані перельоти потребують швидкої й економічної реалізації. Задовольнити зазначені вимоги можна шляхом поєднання участі двигунів великої та малої тяги, які в змозі забезпечити належні потужність й енергоефективність. У пропонованому дослідженні розглянуто задачу "спринтерського" перельоту Земля – Марс, що полягає в переведенні космічного апарату із заданої кругової орбіти навколо Землі на задану кругову орбіту навколо Марсу за заданий час, менший за час класичного перельоту типу Гомана. Комбінування участі двигунів великої та малої тяги приводить до виникнення задачі оптимізації розподілу сумарної характеристичної швидкості маневру між ділянками великої та малої тяги. При цьому рух на геліоцентричній ділянці траєкторії відбувається не за звичайною Кеплерівською траєкторією, а за близькою до неї дугою, що формується двигуном малої тяги. Двигун великої тяги забезпечує маневри у сфері впливу планет. Завдяки цьому, порівняно із класичним варіантом застосування виключно великої тяги, загальний час маневру не змінюється, а частина палива використовується ефективнішою системою малої тяги. Проте виникає питання: за яких умов маса зекономленого в такий спосіб палива перевершить масу додатково встановленої рушійної системи малої тяги. У пропонованій статті отримано оцінку тривалості перельоту, що обмежує зверху інтервал тривалості перельотів, у якому комбінування двигунів великої та малої тяги є оптимальним.
Аналіз ефективності комбінування участі двигунів великої та малої тяги під час перельотів Земля – Марс
Keywords: міжпланетний переліт Земля-Марс; комбінування великої та малої тяги; ядерний двигун; метод транспортуючої траєкторії; Earth – Mars interplanetary flight; combination of high and low thrust; nuclear engine; transporting trajectory method